Evaluation of the evoked brain potentials of patients with asthenia and anxiety symptoms and the partial loss of sight - Abdryakhimova, Tsira; Abdryakhimov, Rostislav; Snegir, Andriy; Kleban, Katherine (Psychosomatic Medicine and General Practice, 2017)
Background. Vision loss, even partial, especially in adulthood, is accompanied by emotional, motivational and social consequences that directly affect the psychophysiological state of the individual himself, his communication in society and, often, the social status of the subject. Methods. From the group of patients-volunteers (n=15) with a partial loss of sight of traumatic genesis two groups were formed for carrying out neurophysiological evaluation: with predominant asthenia and anxiety. The control group (CG) consisted of patients with the same age (n=20) without psychiatric comorbidity. A study of acoustic event-related potentials of the brain (ERP) was carried out in the oddball paradigm with the recording of the time and correctness of a simple sensorimotor reaction. Results. Comparative analysis of the asthenia group with the comparison group revealed a sufficient number of ERP’s, which have significant statistical differences. The correctness of the sensorimotor reaction in this group was 98.3 ± 2.44%, whereas in the CG - 92.5 ± 5.74% (U = 62.5, p<0.01). The P1 initial positivity amplitude values in the asthenia group were 4.25 ± 3.312 μV and in the CG -4.15 ± 7.933 μV (U = 50, p<0.001). The early negativity in that group was -2.78 ± 2.377 μV, and in the CG it was 10.55 ± 7.466 μV (U = 75; p<0.05). Conclusion. In the anxiety group, significant differences were noted in: P1 latency, P1N1, and N2P3 interval latencies, amplitude swing in P1N1. A specific marker of the asthenia group, distinguishing it from the CG, was the more positive values of the amplitude for the components P1, N1, P2, N2. Taking into account the low-frequency nature of the amplitude modulation in these components (circa 2 Hz), it can be assumed that nonspecific brainstem systems are involved in the process.